Wrecked but not Ruined - Ballantyne, R. M. (Robert Michael), 1825-1894 (Salt Lake City, UT : Project Gutenberg, 2007)
"Wrecked but not Ruined" by R. M. Ballantyne is a novel written in the late 19th century, set against the backdrop of the Canadian wilderness. The story follows Reginald Redding, a young fur trader, as he navigates challenges posed by competition from rival settlers, specifically the McLeod family who have begun establishing themselves near his trading post. With themes of survival, territorial disputes, and the exploration of friendships, the narrative sets the stage for encounters that intertwine the lives of the main characters. At the start of the book, we find ourselves at a remote outpost named the Cliff, operated by Reginald Redding and his clerk, Bob Smart. The narrative introduces Redding's concern over the arrival of the McLeods, who threaten to encroach upon his Company's trading rights with their sawmill. The story unfolds with Redding contemplating a journey to confirm the boundaries of his territory. Meanwhile, we meet the McLeods, who are struggling to establish their own identity in the harsh wilderness, all while weaving through interactions filled with tension and camaraderie among characters both familiar and new. The opening chapters set up a rich landscape of conflict, potential friendship, and the beauty and dangers of the untamed Canadian wilderness. (This is an automatically generated summary.)
Release date is 2007-11-06
Produced by Nick Hodson of London, England
Keywords: Canada -- Juvenile fiction; Family -- Canada -- Juvenile fiction; Frontier and pioneer life -- Canada -- Juvenile fiction; French-Canadians -- Juvenile fiction